2010
DOI: 10.5465/19416520.2010.495525
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and International Corporate Governance

Abstract: Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, redistribution , reselling , loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden. The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
330
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 366 publications
(345 citation statements)
references
References 294 publications
10
330
0
5
Order By: Relevance
“…For example, the agency conflict takes on very different forms across countries not only due to the different patterns of shareholder concentration but based on the different social identities of blockholders such as families, the state, banks, foundations or business groups (Jackson, 2010). Institutional theories have moved beyond the focus on how the law shapes agency conflicts, and looks now at how wider cultural, social, and political factors shape the crossnational diversity of actors and settings in corporate governance (for a comprehensive review, see Aguilera & Jackson, 2010).…”
Section: From the Principal-agency Dichotomy Towards A Comparative Inmentioning
confidence: 99%
“…For example, the agency conflict takes on very different forms across countries not only due to the different patterns of shareholder concentration but based on the different social identities of blockholders such as families, the state, banks, foundations or business groups (Jackson, 2010). Institutional theories have moved beyond the focus on how the law shapes agency conflicts, and looks now at how wider cultural, social, and political factors shape the crossnational diversity of actors and settings in corporate governance (for a comprehensive review, see Aguilera & Jackson, 2010).…”
Section: From the Principal-agency Dichotomy Towards A Comparative Inmentioning
confidence: 99%
“…Because corporations and their leaders are embedded in different national systems, they will embrace different societal values related to CSR (Schneider et al 2014;Waldman et al 2006) and experience divergent degrees of internal and external pressures to engage in CSR (Aguilera and Jackson 2010;Doh and Guay 2006;Matten and Crane 2005). For instance, Martin et al (2009), comparing business ethics between managers from Germany and the US, concluded that orientations and approaches to responsible leadership differ.…”
Section: Asian and Western Orientations To Responsible Leadership: Inmentioning
confidence: 99%
“…In these ''stakeholder capitalism'' national models, employees, suppliers, customers and financial institutions are part of the context within which business leaders make decisions and firm performance is evaluated. Firms are expected to protect employee rights, collective bargaining tends to be coordinated, and corporate returns tend to be assessed on a long-term basis (Aguilera and Dencker 2004;Aguilera and Jackson 2010;Witt and Redding 2013). In such an environment, senior executives are more likely to adopt a long-term approach to CSR and focus on a broader group of constituents in their decisions and actions.…”
Section: Asian and Western Orientations To Responsible Leadership: Inmentioning
confidence: 99%
See 1 more Smart Citation
“…to understand the 'mechanisms (used) to ensure that executives respect the rights and interests of company stakeholders, and that those stakeholders are held accountable for acting morally and responsibly for the generation, protection and distribution of wealth invested in the firm' (Aguilera et al 2008, p. 475;Aguilera and Jackson 2010). It is clear from cases in the UK financial services sector that some companies and executives have failed to act responsibly and/ or ethically in balancing their wealth creation and wealth protection roles, in much the same way as their American counterparts (Filatochev 2005;Davis 2009;Smallman, et al 2010;Kerr and Robinson 2011).…”
Section: Introductionmentioning
confidence: 99%